S104 Investigating the diagnostic performance of specific immunological tests in occupational asthma. (15th November 2017) - Fernandes, D; Cannon, J; Fitzgerald, B; Welch, J; Jones, M; Cullinan, P; Szram, J
Abstract : The detection (or otherwise) of specific IgE sensitisation is an important tool in the investigation of employees with potential occupational asthma from high molecular mass agents. 1 We investigated the diagnostic performance of skin prick testing (SPT) and serum specific IgE (sIgE) in patients referred to a specialist clinic. Data from wheat flour sIgE (n=295) and SPTs (n=322) were compared to each other, as well as to results from specific inhalation challenge (SIC) to wheat flour (n=22). Mouse and rat sIgE (n=156 and n=143 respectively) and SPTs (n=166 and n=137 respectively) were compared against diagnosis by expert clinician. Sensitivity, specificity, and positive and negative predictive values were calculated at different IgE concentrations and wheal sizes and optimal cut offs, maximising sensitivity and specificity, were generated. Receiver-operating characteristics (ROC) plots were generated, taking either SIC or sIgE and clinical diagnosis as the gold standard for diagnosis; area under the curve (AUC) was calculated. Using SIC as a gold standard, ROC curves (figure 1 A) demonstrated wheat flour-sIgE to be a more accurate test than SPT in predicting occupational asthma (AUC 0.88 compared with AUC 0.77); an optimal cut-off for sensitivity and specificity for sIgE of ≥1 kU/L was calculated. This new cut-off was then used to identify an optimum cut-off for SPT to wheat flour of 2.5 mm was identified. Optimal cut-offs for mouse and rat protein SPT of ≥2 mm and ≥1 mm for sIgE and ≥1 kU/L and ≥0.35 kU/L respectively were calculated. Conclusion: In this population, sIgE for wheat flour and rat proteins was more accurate than SPT at predicting occupational allergic disease; the opposite was true for mouse allergens. The standard 'cut-off' for sIgE ≥0.35 kU/L is sufficient for rodent allergens but may lack specificity in bakers. Reference: van Kampen V, Rabstein S, Sander I, Merget R, Bruning T, Broding HC, et al . Prediction of challenge test results by flour-specific lgE and skin prick test in symptomatic bakers. Allergy 2008;63(7):897–902.